Understanding the links between agriculture and health: Overview - Hawkes, Corinna; Ruel, Marie T. (International Food Policy Research Institute, 2006)
Good health and productive agriculture are both essential in the fight against poverty. In a rapidly changing world, agriculture faces many challenges, both old (natural resource constraints, extreme weather conditions, and agricultural pests) and new (globalization, environmental degradation, problems of maintaining production in conflict situations). At the same time, new global health threats emerge, such as HIV/AIDS, SARS, and avian influenza, while old ones persist. Not only do malaria, tuberculosis, diarrheal diseases, respiratory infection, and malnutrition continue to take a heavy toll, but the health sector is faced with increasing problems of chronic disease, drug and insecticide resistance, and a diminishing arsenal of effective interventions. And as the world becomes more integrated, so do the agricultural and health problems the world faces... The briefs in this series aim to communicate what is known about the linkages between agriculture and health in science and policy, thereby stimulating interest in and dialogue on agriculture and health. With a focus on the poor in developing countries, the briefs deal with the relationship between agricultural producers, systems, and outputs and the world’s leading causes of death and disease. They examine the various trade-offs involved and set out some of the approaches needed to create improved synergies between the agricultural and health sectors.